Aplikasi Augmented Reality Sebagai Media Pembelajaran Tempat Bersejarah Berbasis Android Di Kota Tangerang: History Learning Using Augmented Reality - Nugraha, Panji; Ridwan, Mohammad; Sukrim, Sukrim (Jutis (Jurnal Teknik Informatika), 2023)
Information technology is currently developing rapidly, especially in the field of mobile technology, cell phones are now used for various activities outside of communication, especially in the field of online learning. Mobile learning is online learning that uses information technology in the learning process, such as using smartphones as an easy-to-use learning media. learning media applied in children's learning places generally use books, children's magazines, pictures and others. For example, when children learn to read, count, learn to recognize things such as pictures of monuments, heroes or historical places, they use picture books, photos or props that make students bored. Augmented reality can make the unreal can enter the real world through augmented reality by pointing the smartphone camera at the marker or marker that has been provided then on the smartphone screen will appear 3D objects. This learning uses the REACT strategy which has positive potential in helping students' understanding and thinking skills through the stages that students will go through. Teaching children using Augmented reality can bring the virtual world into the real world as a solution to the problems that have been described, the innovation that will be made is the introduction of historical places using android-based augmented reality in Tangerang City which is flexible and has a new attraction in the field of historical learning media.